Nowhere-zero 3-flows in graphs admitting solvable arc-transitive groups of automorphisms - Li, Xiangwen (Ars mathematica contemporanea, 2016)
Tutte's 3-flow conjecture asserts that every 4-edge-connected graph has a nowhere-zero 3-flow. In this note we prove that every regular graph of valency at least four admitting a solvable arc-transitive group of automorphisms admits a nowhere-zero 3-flow.
Keywords: arc-transitive graph; celoštevilski tok; integer flow; ločno-tranzitiven graf; nikjer-ničeln 3-tok; nowhere-zero 3-flow; rešljiva grupa; solvable group; vertex-transitive graph; vozliščno-tranzitiven graf